Strategies to Create Competitive Advantage Through Promotions at Samana Resto Villa and Catering - I Gusti Made Oka Astana (Universitas Pendidikan Ganesha, 2021)
This study aims to create excellence compete at the Samana Resto Villa and Catering. Data collection techniques used in. This study uses documentation techniques and interview techniques with several informants. The results of this study explain that based on the results of the VRIO analysis obtained from interviews with several informants, it was found that there were 18 resource and capability that can be specified are 8 tangible resource competencies and resources There are 6 intangibles while for the capabilities there are 4. Competencies owned Samana Resto Villa and Catering more from a resource aspect than capabilities because resource competencies are 14 and there are 4 competencies. Based on 18 resources and capability included in the highly rated category need a new strategy such as for the resources there are strategies that can be done, namely from Human resources, by involving human resources in workshops, seminars or training regarding the Resto Villa and Catering industry as well as increasing the number of competent employees in the hospitality industry; Facility strategy can be done with maximize the use of the internet as a means of promoting the dissemination of information as well as a branding tool; Location, to draw visitors are not only a strategic location but also need cooperation with travel parties and tour agents, because this strategy can be done as a means promotions and branding; The use of technology can have done by leveraging android to increase promotion and increase services with android applications. While the strategy that can be done from the side Capabilities; Service Skills with care improve employee abilities in serving visitors and improving language skills by following training; networking skills, this can be done by increasing the number network and cooperation so as to create new networks and can improve number of visitors.